Influence Of Service Quality, Location dnd Facilities For The Decision To Visit Back At The Promise Soul Cafe, Bengkulu City - Valentina, Femmy; Arini, Eti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of service quality on the decision to return to the Promise Jiwa Tanah Patah Cafe in Bengkulu City, to determine the location that influences the decision to return to the Promise Jiwa Tanah Patah Cafe in Bengkulu City. To find out which facilities influence the decision to return to the Promise Jiwa Tanah Patah Cafe in Bengkulu City and to find out the quality of service locations and facilities simultaneously influence the decision to return to the Promise Jiwa Tanah Patah Cafe in Bengkulu City. This research is a type of quantitative research. Data collection techniques are observation, documentation and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of the study it was concluded that: Service quality (X1) influences the decision to visit (Y) at Cafe Janji Jiwa Bengkulu, meaning that if the quality of service increases, the decision to visit also increases. Location (X2) influences the decision to visit (Y) at Cafe Janji Jiwa Bengkulu, meaning that if the location increases, the decision to visit also increases. Facilities (X3) affect the decision to visit (Y) at Cafe Janji Jiwa Bengkulu, meaning that if the facilities increase, the decision to visit also increases. Service quality (X1), location (X2) and facilities (X3) affect the decision to visit (Y) at the Bengkulu Jiwa Cafe, meaning that if the quality of service, location and facilities increases, the decision to visit also increases.